Prinsip Non-Refoulement Penanganan Pengungsi dan Relevansinya dalam Perspektif Kebijakan Selektif Keimigrasian - Fitri, Icha Rachma Mutiara; Yepese, Jehan Irianti Bekti; Arofah, Mochamad Gozzi (Universitas Batanghari Jambi, 2024)
Immigration is a matter of the movement of people into and out of Indonesian territory which is motivated by several factors such as socio-cultural, political and economic which are the reasons why foreigners migrate. The Immigration Office is under the Directorate General of Immigration and is the responsibility of the Ministry of Law and Human Rights and has the authority to regulate the presence and activities of foreigners while they are in Indonesian territory. Immigration adheres to a selective policy system, which means that only useful and useful foreigners are allowed to enter Indonesian territory and do not disturb the country's sovereignty. International law applies the principle of non-refoulement, namely prohibiting the expulsion or refusal of foreigners to return to their country of origin for certain reasons. This principle aims to protect the human rights of refugees. National interests are not linear with international legal interests. Therefore, refugees cannot be separated from Immigration's responsibility in carrying out supervision and providing enforcement of immigration law. This research uses a normative-empirical research method which refers to the provisions in primary and secondary legal studies. Researchers collect related data from legal principles, legal conceptions, views, legal doctrines, statutory regulations and the legal system as the main focus.